2015
DOI: 10.17772/gp/59023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbetocin and oxytocin efficiency in preventive tretment of postpartum hameorrhages referred to women after cesarean section.

Abstract: StreszczenieKrwotok poporodowy (postpartum haemorhage -PPH) stanowi najważniejszą przyczynę zgonów okołoporodowych wśród kobiet na świecie. Identyfikacja czynników ryzyka oraz znajomość zasad profilaktyki i postępowania w PPH pozwalają ograniczyć ilość utraconej krwi. W profilaktyce PPH zastosowanie znajdują: oksytocyna, karbetocyna, metylergometryna, dinoprost, sulproston, mizoprostol. Cel pracy: Ocena i porównanie skuteczności karbetocyny i oksytocyny w profilaktyce krwawień poporodowych u kobiet po cięc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Jagielska et al compared the effects of carbetocin and oxytocin on PPH after cesarean section. They found that although the reductions in the levels of hemoglobin and hematocrit 24 h after cesarean section were greater in women who received oxytocin than in those who received carbetocin, the difference was not significant (hemoglobin − 1.24 vs. 1.17 g/dl; hematocrit − 3.26 vs. 2.93%) [ 27 ]. Also, Leung et al, in their study on 329 women who randomized in two groups of carbetocin (100 μg IM) or ergometrine (0.5 mg IM), found that the need to additional uterotonic agents, postpartum hemorrhage, and retained placenta was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Jagielska et al compared the effects of carbetocin and oxytocin on PPH after cesarean section. They found that although the reductions in the levels of hemoglobin and hematocrit 24 h after cesarean section were greater in women who received oxytocin than in those who received carbetocin, the difference was not significant (hemoglobin − 1.24 vs. 1.17 g/dl; hematocrit − 3.26 vs. 2.93%) [ 27 ]. Also, Leung et al, in their study on 329 women who randomized in two groups of carbetocin (100 μg IM) or ergometrine (0.5 mg IM), found that the need to additional uterotonic agents, postpartum hemorrhage, and retained placenta was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%